Heterogeneity and longitudinal transcriptomic characteristics of Tregs in COVID-19 patients - Wen, Yanling; Zhao, Juanjuan; Zhang, Zheng (Frontiers in Immunology, 2025)
IntroductionRegulatory T cells (Tregs) play a crucial role in maintaining immune tolerance by suppressing immune responses against pathogens. The fluctuation of Treg proportions in COVID-19 remains a topic of debate, and the mechanisms triggering Treg activation in COVID-19 are still unclear. Understanding these issues is essential for better managing immune responses in COVID-19 patients.MethodsWe collected a cohort of COVID-19 patients with varying disease severity and stage to explore the transcriptomic and functional traits of Tregs in these individuals. Using transcriptomic analysis, we evaluated the proportion and functionality of different Treg subsets, specifically HLA_DR+ Tregs, across different stages of COVID-19 patients.ResultsOur analysis revealed that the proportion of CCR7+ Tregs decreased as the disease advanced, while the cell proportion of HLA_DR+ regs escalated with the severity of the disease. Moreover, the transcription actor CARHSP1 exhibited apositive correlation with the proportion of HLA_DR+ Tregs. Notably, the heightened suppressive function of HLA_DR+ Tregs in severe COVID-19 patients, with interactions between PF4 and CXCR3, contributed to the homeostasis of HLA_DR+ Tregs in severe COVID-19 patients. Furthermore, we observed that Tregs in COVID-19 patients exhibited weakened TCR clonotype expansion, and the suppression of HLA_DR+ Tregs with expanded TCR clonotypes in severe COVID-19 cases did not show a significant increase compared to asymptomatic and mild COVID-19 groups. The findings indicate that Tregs may be activated through the bystander effect, as evidenced by the analysis of TCR clonotype characteristics.DiscussionOur research delineates the diversity of dynamic alterations in Tregs and sheds light on potential mechanisms underlying Treg activation, providing a theoretical foundation and offering treatment strategies for managing COVID-19 patients.